Hubungan Jarak Rumah dari Tempat Penampungan Sementara dengan Gangguan Bau yang di Rasakan Masyarakat Lorong Tekukur - Siti Rabbani Karimuna; Riska Riska; Rezki Aulia; Zahratun Nisa; Ramlia Wati (Universitas Muhammadiyah Manado, 2026)
In the waste management system, a Temporary Waste Storage Site (TPS) functions as an intermediate facility for transferring waste from collection points to transportation vehicles before reaching the final disposal site and may also serve as a waste sorting location. This study aimed to analyze the relationship between the distance of residential houses from the Temporary Waste Storage Site and odor disturbances perceived by residents of Lorong Tekukur. A quantitative method with an observational analytic design and cross-sectional approach was employed. The study involved 30 respondents selected through total sampling. Data were collected through face-to-face interviews using structured questionnaires and analyzed using univariate and bivariate analyses with the chi-square test. The results showed that most respondents had good knowledge, with 20 respondents (66.7%) categorized as having good knowledge, 6 respondents (20.0%) moderate knowledge, and 4 respondents (13.3%) poor knowledge. Regarding compliance with the recommended distance between residential houses and the Temporary Waste Storage Site related to odor disturbances, 28 respondents (93.3%) were categorized as good, while 2 respondents (6.7%) were categorized as poor. The chi-square test showed a significant relationship between community knowledge and compliance with the recommended distance from the Temporary Waste Storage Site (p = 0.006; p < 0.05). Strengthening community education and environmental management practices is needed to reduce odor impacts and improve waste management effectiveness.